A large-scale organoid-based screening platform to advance drug repurposing in pancreatic cancer - Sara Mainardi; Rene Bernards (Cell Genomics, 2022)
Hirt et al.1 report an automated, high-throughput drug screening platform for organoid cultures to enable repurposing of previously approved drugs for pancreatic cancers harboring specific genetic alterations. The pancreatic cancer organoid biobank also represents a valuable tool to uncover new drug-gene interactions in pancreatic tumors.